Modeling of the mesenchymal stem cell microenvironment as a prospective approach to tissue bioengineering and regenerative medicine (a short review) - I. A. Khlusov; L. S. Litvinova; K. A. Yurova; E. S. Melashchenko; O. G. Khaziakhmatova; V. V. Shupletsova; M. Yu. Khlusova (Бюллетень сибирской медицины)
One of the promising areas is the design and modification of materials for control over the fate of multipotent mesenchymal stromal cells (MMSCs) that will allow stroma of various human and animal organs and tissues to be constructed. However, the discussion about the existence and functioning of microenvironment for the MMSCs is just beginning to develop. The design of artificial materials that are able to reproduce biomimetically the cellular and tissue microenvironment and based on ideas and main elements borrowed from wildlife is current direction in a development of medical materials technology and tissue bioengineering. Scaffold technology is a promising experimental approach to simulate the properties of natural microenvironment of stem cells. Our aim is a short review of key elements of MMSC microterritories, its advanced investigations and the attempts of modeling in application to tissue bioengineering and regenerative medicine.